Questions kids ask about everyday life - Comely, Richard; Dickie, Alison (Grolier Toronto, 1989)
Questions Kids Ask About Everyday Life provides insightful answers to children's questions about daily routines, helping them understand the world around them and encouraging curiosity about the ordinary things in life.